PENERAPAN DESIGN THINKING PADA SAYURBOX - Ginanjar, Jajang; Sukoco, Iwan (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2022)
This research intends to explain each stage in Design Thinking carried out by Sayurbox (PT Kreasi Nostra Mandiri). The method used for this research is qualitative with descriptive analysis and also explained through the theory of David Kelley and Tim Brown. The results of this research, Sayurbox (PT. Kreasi Nostra Mandiri) has manifested various solution that initially only made offers via WhatsApp & Instagram into a form of online based special application by utilizing the implementation of design thinking. In addition, Sayurbox has succeeded in completing features by not being limited to only agricultural products but expanding more widely with fast-moving consumer products, so that Sayurbox can reach a wider range of customers based on their preferences.